Diagnostic accuracy of dynamic gadoxetic‐acid–enhanced MRI and PET/CT compared in patients with liver metastases from neuroendocrine neoplasms. Issue 2 (18th December 2013) - Armbruster, Marco; Zech, Christoph J.; Sourbron, Steven; Ceelen, Felix; Auernhammer, Christoph J.; Rist, Carsten; Haug, Alexander; Singnurkar, Amit; Reiser, Maximilian F.; Sommer, Wieland H.
<x xml:space="preserve">Abstract</x> Purpose To evaluate the diagnostic accuracy of dynamic‐contrast–enhanced (DCE) MRI in comparison to both 18F‐FDG‐ and 68Ga‐DOTATATE‐PET/CT in patients with liver metastases of neuroendocrine neoplasms (NEN). Materials and Methods Thirty‐two patients with hepatic metastases from NEN were examined both in DCE‐MRI and positron emission tomography/computed tomography (PET/CT), using either 18F‐fluorodeoxyglucose (18F‐FDG) or 68Ga‐DOTATATE as tracer. DCE‐MRI was performed at 3 Tesla with Gd‐EOB‐DTPA acquiring 48 slices every 2.2 s for 5 min. Three regions of interest (ROIs) representing liver background and liver metastases were defined in fat‐saturated T1w three‐dimensional GRE MRI sequences in the hepatobiliary phase. Corresponding ROIs were then defined in the DCE‐MRI‐ and in the PET/CT‐dataset. Area under the curve (AUC) was calculated for the differentiation between metastases and liver background for DCE‐MRI and PET‐CT parameters. Results AUC was very high for SUVmean (mean standardized uptake value) derived from 68Ga‐DOTATATE‐ (AUC = 0.966), and 18F‐FDG‐PET/CT (AUC = 0.989). For DCE‐MRI parameters, arterial flow fraction and intracellular uptake fraction showed the highest AUCs (AUC = 0.826, AUC = 0.819, respectively). The combination of those two had an AUC of 0.949. The combination of DCE‐MRI and PET‐CT parameters resulted in the highest AUC. Conclusion Both PET/CT parameters and DCE‐MRI perfusion parameters show a high diagnostic accuracy in the distinction between liver metastases and liver tissue. Our data suggest that both modalities provide complementary information. J. Magn. Reson. Imaging 2014;40:457–466. © 2013 Wiley Periodicals, Inc.